Bridging cultures: Malaysian-Japanese inspirations in pop-up design storytelling - Subri, Shafilla; Wan Omar, Wan Noor Faaizah (Universiti Teknologi MARA, Kedah, 2025)
Entrepreneurship extends beyond simple product sales, encompassing the development of experiences that personally and emotionally connect with individuals. Design is pivotal in defining experiences, and for young entrepreneurs in Malaysia, narrative through design acts as a potent means of differentiation.